Excited States Calculations of MoS2@ZnO and WS2@ZnO Two-Dimensional Nanocomposites for Water-Splitting Applications - Lin, Yin-Pai; Polyakov, Boris; Butanovs, Edgars; Popov, Aleksandr A.; Sokolov, Maksim; Bocharov, Dmitry; Piskunov, Sergei (MDPI, 2022)
Transition metal dichalcogenide (TMD) MoS2 and WS2 monolayers (MLs) deposited atop of crystalline zinc oxide (ZnO) and graphene-like ZnO (g-ZnO) substrates have been investigated by means of density functional theory (DFT) using PBE and GLLBSC exchange-correlation functionals. In this work, the electronic structure and optical properties of studied hybrid nanomaterials are described in view of the influence of ZnO substrates thickness on the MoS2 @ZnO and WS2 @ZnO two-dimensional (2D) nanocomposites. The thicker ZnO substrate not only triggers the decrease of the imaginary part of dielectric function relatively to more thinner g-ZnO but also results in the less accumulated charge density in the vicinity of the Mo and W atoms at the conduction band minimum. Based on the results of our calculations, we predict that MoS2 and WS2 monolayers placed at g-ZnO substrate yield essential enhancement of the photoabsorption in the visible region of solar spectra and, thus, can be used as a promising catalyst for photo-driven water splitting applications. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.--//-- Published under the CC BY 4.0 licence.
This research was funded by the Latvian Scientific Council grant LZP-2018/2-0083. Institute of Solid State Physics, University of Latvia, as the Center of Excellence, has received funding from the European Union's Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Density functional theory; Excited state calculations; MoS2 @ZnO and WS2 @ZnO nanostructures; Photoabsorption; Photocatalyst